The global economic crisis : systemic failures and multilateral remedies (UN New YorkUS, 2009)
Highlights three specific areas in which the global economy experienced systemic failures. Examines some facets to the crisis that are considered to be the core areas to be tackled immediately by international economic policy-makers because they can only be addressed through recognition of their multilateral dimensions. Investigates three interrelated issues of importance to developed and developing countries alike and proposes measures to address the systemic failures they have entailed.
Keywords: ECONOMIC RECESSION